HUBUNGAN PERSEPSI KINERJA PEMERINTAHAN DENGAN KETERPILIHAN CALON PASANGAN PETAHANA DI PILKADA SALATIGA 2017 - Aris Tri Haryanto, Suwardi & (Transformasi, 2017)
The 2017 Major Election of Salatiga concluded that the number of earned votes for currentMajor and Vice-Major Yulianto – Muhammad Haris (Yaris) surpass the earned votes for Agus Rudianto –Dance Palit Ishak (Rudal). As the incumbent, Yaris were much favored politically. Strategic incumbentvariable is a chance to convince public over their government performance. The level of publicsatisfaction over the performance of Major Yulianto could be the main modal to build personal politicalvariable such as popularity, acceptability and electability.This Research use survey data that conducted by the researcher while the 2017 Major Election ofSalatiga is on process. The survey data then analyzed using determination approach with the result of the2017 Major Election of Salatiga that being held on 15 February 2017. Aspect of the method used in thissurvey are using sample frame of Permanent voters list (DPT). The technique used to get the sample arecuplikan random sampling based on the survey location. The survey conduected over 96 TLS with 768reponden. This survey has 3,5% margin error with significance level of 95%.Yaris perceived to have good governing performance of 77%. This incumbent win the electionwith 50,5% earned votes. At the unit level data analysis, 23 kelurahan indicates the distribution arevaries. Although there is a relation between good governing performance and the incumbent to beelected, there are many other variable that affect the result.Key word: local election, Salatiga, incumbent, performance,political personal